A Performance Study of ATM Multicast Switch with Different Traffics - Hambali, Hamirul’Aini; K. Ramani, Ashwani (Malaysian Journal of Computer Science, 2002)
The demand of multicast service in ATM networks such as video teleconferencing and large file transfer makes the multicast switch very important. Since the cell loss and delay will decrease the performance of an ATM multicast switch, this paper proposes a new architecture of the switch. To improve the performance, this paper classifies traffic into three categories with different requirements: real-time traffic, near real-time traffic and non real-time traffic. The proposed architecture with the above traffic classes is studied by developing appropriate simulation models. Subsequently, the effects of arrival rate and immediate rate on the switch performance are studied quantitatively and qualitatively. It is concluded that the proposed architecture can support different future types of multimedia traffic, where cell loss probability and delay requirement will be the main factors.